Women rights to inheritance in Muslim family law: an analytical study - Haque, Muhammad Faizul; Solihin, Sohirin Mohammad; Ahmad, Nadzrah; Jani, Mohd. Shah (2020)
Rights of women are one of the widely discussed yet debatable issues across the Western and Muslim world. It is seen in the Muslim societies that many women are deprived in terms of inheriting property after the demise of their parents. This is largely happening due to the negligence of practicing Islamic teachings regarding inheritance at individual and family level. However, Islam has placed a dignified position for women in family and society in all sectors. Particularly the principle of inheritance of property has been clearly stated in the holy Qur’an. In this background, this paper emphasises on exploring (a) Qur’anic and Prophetic stand on women’s right to inheritance, (b) the main obstacles that impede women in getting inheritance rights in family and its remedies from the Islamic perspectives. This paper adopts an analytical approach to study this vital issue. Under this approach, the study analyses the relevant data from the two fundamental sources of Islam, Qur’an and Sunnah, along with jurisprudential views and provides solutions to solve the problems related to Muslim women’s inheritance right in family. Findings of this paper indicated that if the Muslim family practices the Islamic teachings regarding the distribution of inheritance among the heirs, it will eradicate the existing discrimination among men and women in this regard and enable women’s financial steadiness in family and society.